Pengaruh Posisi Runway 13/31 dan 03/21 Terhadap Layanan Ground Control Unit di Bandar Udara Internasional Sultan Hasanuddin Makassar - Sabur, Fatmawati (Politeknik Penerbangan Makassar, 2018)
Safe and seamless flight traffic services are the right of consumers as service users, where the smoothness of traffic is influenced by human resources, service procedures and facilities used in providing aviation traffic services. Hasanuddin Makassar International Airport has experienced significant movement of aircraft for the last 5 years using Multiplerunway. The purpose of this research is to know the effect of multiplerunway 13/31 and 03/21 on the efficiency of Aerodrome Control Tower service delivery. The research method is qualitative descriptive analysis using runway 03/21 and runway 13/31. Runway configuration 03/21 and 13/31 unusual angular shape requires ATC to follow Multiple Runway Operation and Standard Operating Procedure in determining runway-use. The use of multiplerunway, not fully optimal for ATC in giving instruction of aerodrome control service because it still takes 6 - 8 minu/te departure process with runway in use 03/21 while departure process using runway in use 13/31 takes maximum 10 - 15 minutes.